PERAN SERTA MASYARAKAT DALAM PELESTARIAN OBJEK WISATA AIR TERJUN NUNGNUNG DI DESA ADAT NUNGNUNG KABUPATEN BADUNG - Paramita, Ida Bagus Gede; Tirtayasa, Wayan (Maha Widya Duta: Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2017)
Natural beauty is a tourism asset besides Balinese customs and culture, Nungnung waterfall is a tourism ass et as well as being a cultural preservation owned by the Badung regency. Even though it has received serious attention from the Badung Regency Government, this area lacks proper and proper management so that it seems less than optimal. This area is classified as a historic and rare area. The reason is that there is a lack of maximum community involvement in guarding the tourist sites, so conservation needs to be held to educate the public about the sustainability and existence of these objects. Which in turn can generate income for the surrounding community.Keywords: Community Participation and Conservation of Nungnung Waterfall Tourism Objects